Community policing : national and international models and approaches - Brogden, Michael (Willan, 2005)
Community policing has been a buzzword in Anglo-American policing for the last two decades, somewhat vague in its definition but generally considered to be a good thing. In the UK the notion of community policing conveys a consensual policing style, offering an alternative to past public order and crime fighting styles. In the US community policing represents the dominant ideology of policing as reflected in a myriad of urban schemes and funding practices, the new orthodoxy in North American policing policy-making, strategies and tactic. But it has also become a massive export to non-western s.